Consumers’ preferences for rice attributes in Cambodia: a choice modeling approach - Bairagi, S.; Mohanty, Samarendu; Custodio, M.C. (Emerald Publishing Limited, 2019)
The purpose of this paper is to examine rice attributes that are valued by the urban consumers of Cambodia and identifies the factors that influence consumers' decisions on a set of rice attributes. The study uses incomplete ranking choice data, gathered from a stated preference survey conducted from 350 consumers of two cities in Cambodia, to model consumers' alternative choices of rice traits in a setting of a random utility framework. Empirically, a rank-ordered logistic regression is fitted to identify the factors influencing consumers' perception on a set of rice attributes. The results suggest that the probability of choosing rice that is soft is highest for consumers in Cambodia. The second and third most preferred rice attributes are taste and aroma, respectively. The results also indicate that rice consumption is significantly affected by location, economic class of consumers, family size and educational attainment.